Design study of integrated photonic transmitters for application in Fiber-to-the-Home networks - Ławniczuk, Katarzyna; Piramidowicz, Ryszard; Szczepański, Paweł; Smit, Meint; Leijtens, Xaveer (Photonics Letters of Poland, 2010)
Different solutions of photonic transmitters based on arrayed waveguide gratings are demonstrated. The basic concepts of realizing integrated multiwavelength lasers with optical modulators are presented and discussed in detail. Full Text: PDF References M. K. Smit, "New focusing and dispersive planar component based on an optical phased array", Electron. Lett. 24(7), 385 (1988). [CrossRef] M.K. Smit, 3rd Int. conference on Optics-photonics Design and Fabrication, 51-52, Tokyo 1, 30 Oct. - 1 Nov. 2002, Optical Society of Japan, 2002. J.H. den Besten, Integration of Multiwavelength Lasers with Fast Electro-Optical Modulators, PhD Thesis, 2004. B.Docter, Deeply-Etched DBR Mirrors for Photonic Integrated Circuits and Tunable Lasers, PhD Thesis, 2009. S. C. Nicholes, M. L. Masanovic, B. Jevremovic, E. Lively, L. A. Coldren, and D. J. Blumenthal, "An 8$,times,$ 8 InP Monolithic Tunable Optical Router (MOTOR) Packet Forwarding Chip", J. Lightwave Techn. 28(4) Feb. (2010).[CrossRef] R.Broeke, A Wavelength Converter Integrated with a Discretely Tunable Laser for Wavelength Division Multiplexing Networks, PhD Thesis, 2003. F.M. Soares, J.H. Baek, N.K. Fontaine, C. Junesand, S. Lourdudoss, K.Y. Liou, R.A. Hamm, W. Wang, B. Patel, W.S. Hobson, J.R. Lothian, S. Vatanapradit, L.A. Gruezke, W.T. Tsang, and S.J.B. Yoo, Optical Fiber Communications Conference, Paper OThS1, 2010. H. Yang, M. Chin, J. Zhou, S. Lee, W. Chen, and H. Zhu, "A traveling-wave electroabsorption modulator with a large optical cavity and intrastep quantum wells", Semicond. Sci. Technol. 23, 105011 (2008).[CrossRef] J.H. den Besten, D. Caprioli, W. Pascher, R. van Dijk, X.J.M. Leijtens, M.K. Smit, "Simulation and design of a 40 GHz Mach?Zehnder modulator on InP", Proceedings of the Symposium on IEEE/LEOS Benelux Chapter, Amsterdam, 2002, pp. 123?126 H.N. Klein, H. Chen, D. Hoffmann, S. Staroske, A.G. Steffan, K.-O. Velthaus, "1.55?m Mach- Zehnder Modulators on InP for Optical 40/80 Gbit/s Transmission Networks", International Conference on Indium Phosphide and Related Materials Conference Proceedings, 171?173, 2006[CrossRef]